Epidemiology and risk factors associated with gout control among adult Asians: a real-world retrospective cohort study - Oka, Prawira; Chong, Wei Ming; Ng, Ding Xuan; Aau, Wai Keong; Tan, Ngiap Chuan (Frontiers in Medicine, 2023)
Background: Gout is associated with significant morbidity and mortality, yet suboptimal gout control remains a problem globally. Identifying the risk factors associated with poor gout control among patients in primary care allows targeted interventions to improve their clinical management. This study aimed to determine the prevalence of poor gout control and its associated demographic and clinical factors among urbanised community-dwelling Asian patients.Methods: This retrospective study was based on data extracted from the electronic medical records of 8 public primary care clinics in Singapore. Patients with a diagnostic code of gout who had 2 or more visits between 1 st January 2018 and 31 st December 2019 were included in the analysis. Data extracted included: demographics, anthropological measurements, comorbidities, serum uric acid levels and medication prescription. A patient is defined to have poor gout control if they suffer two or more acute gout attacks within a year. Chi-Squared test was used for categorical parameters. For continuous variables, univariate logistic regression analysis was first performed. Significant factors (p≤0.1) were then included in the logistics regression model to account for confounders.Results: A total of 7,970 patients and 24,624 visits were included in the analysis. The prevalence of poorly controlled gout was 28.2% (n=2,244/7,970); only 46.3% of them (n=1,039/2,244) were prescribed allopurinol and 13.4% (n=301/2,244) were taking doses ≥300mg. Using logistic regression, factors associated with poor gout control were: male gender (adjusted OR [AOR] =1.66, p<0.001), Malay ethnicity (AOR=1.27, p=0.007), congestive heart failure (AOR=1.64, p=0.037). Patients prescribed allopurinol (AOR=1.52, p<0.001), NSAIDs (AOR=2.76, p<0.001) and corticosteroids (AOR=2.83, p<0.001) were more likely to have poorly-controlled gout.Nearly 30% of patients had poor gout. Interventions should focus on male and Malay patients and those with congestive cardiac failure.